IN SITU STRUCTURAL INVESTIGATION OF IRON-CONTAINING SILICATE LIQUIDS AND GLASSES - Wang Z.; Cooney T.F.; Sharma S.K. (My University, 1995)
In situ high-temperature Raman spectra are presented below and above the glass transition temperature (Tg) of the 0.5Na2O.0.5Fe2O3.3SiO2 (Fe-albite, NFS0), 1.5Na2O.0.5Fe2O3.3SiO2 (NFS2), K2O.0.5Fe2O3.3SiO2 (KFS), and reduced K2O.FeO.3SiO2 (KFS-R) compositions. For the oxidized sample, there is a close structural relationship between the glass and the super-cooled melt above Tg. With increasing temperature, no coordination changes of Fe3+ and no new anionic species are observed in the oxidized melts. In the spectrum of fully polymerized Fe-albite (Fe-Ab) glass, the increase in linewidth of the low frequency Raman band at 452 cm-1 and shift in the position of the band to higher frequency at high temperature indicate an increase in the extent of disorder and decrease of average T-O-T angle, where T = Si, Fe3+ in tetrahedral coordination. In the depolymerized glasses, (NFS1) and KFS, the increase in intensities of the Raman bands associated with Q3 species, containing three bridging oxygen atoms per T cation, result from either a change in relative cross sections of Raman modes or from a net increase in Q3 species with increasing temperature. On the basis of observed changes in the Raman spectra of the reduced sample (KFS-R), it is proposed that most of the Fe2+ ions act as network modifier. This suggestion is justified by the observation of the polarization character of the spectra and the appearance of new Raman bands.